Leptus (Leptus) simonettae Haitlinger, 2000 (Trombidiformes: Erythraeidae) parasitizing a soft tick (Ixodida: Argasidae) in Brazil - Bassini-Silva, Ricardo (2019)
Leptus Latreille is the most diverse genus of Erythraeidae Robineau-Desvoidy, with 275 species (based on larval stage) worldwide described. Their larval stage parasitizes different species of arthropods. Until date, 12 species of Leptus have been registered for Brazil. In this study, we identified for the first time a larva of Leptus parasitizing an adult Ornithodoros soft tick in Brazil. This is the first record of a mite parasitizing an argasid tick, and increases the known number of Leptus in Brazil to 13.